Kinetic and thermodynamic evaluation of sulfonated guar gum-based hydrogels for effective and rapid adsorption of cationic dyes - Chauhan, Sandeep; Kumar, Puneet; Chauhan, Ghanshyam S.; Ranote, Sunita; Jamwal, Pooja; Kumar, Kiran (Journal of dispersion science and technology, 2025)
To develop new sustainable and efficient materials for green technologies, we report the synthesis of guar gum (GG) and 2-Acrylamido-2-methylpropanesulfonic acid (AMPSA) based hydrogels for the removal of cationic dyes. GG was grafted with AMPSA and crosslinked with different concentrations (1, 2.5, and 5%) of ethyleneglycoldimethylacrylate (EGDMA) to obtain GG-g-poly(AMPSA)-cl-EGDMA hydrogels. The well-characterized hydrogels were investigated for adsorption of two cationic dyes, malachite green (MG) and crystal violet (CV). The hydrogel with 2.5% EGDMA showed the best dye uptake and was thus further investigated for the uptake of dyes. The selectivity of the hydrogels for cationic dyes was established by comparing the adsorption capacity of cationic and anionic dyes from their binary solutions. The role of the sulfonate group in the removal of the cationic dyes was established with two control experiments using pristine GG and GG hydrogel with 2.5% EGDMA but without AMPSA. The hydrogel showed tremendous dye adsorption with percent uptake up to 93.13% for MG, 91.50% for CV, and 91.8% for the mixture of dyes in 45 minutes. The adsorption followed pseudo-second-order kinetics and Langmuir adsorption isotherm with a maximum adsorption capacity of 354.6 mg/g and 163.39 mg/g for CV and MG, respectively. The adsorbent exhibited good regeneration and recyclability up to seven cycles. Finally, dye adsorption studies of the candidate hydrogel were carried out for real textile effluent. The reported GG-g-poly(AMPSA)-cl-EGDMA hydrogels possess great potential as cost-effective, sustainable, recyclable, and environmentally-friendly adsorbents for the selective and effective removal of hazardous cationic dyes from wastewater.